2003
DOI: 10.1007/s00442-003-1268-6
|View full text |Cite
|
Sign up to set email alerts
|

Sex-biased movement in the guppy ( Poecilia reticulata )

Abstract: The movement strategies of birds and mammals are often closely linked to their mating system, but few studies have examined the relationship between mating systems and movement in fishes. We examined the movement patterns of the guppy ( Poecilia reticulata) in the Arima river of Trinidad and predicted that sexual asymmetry in reproductive investment would result in male-biased movement. Since male guppies maximize their reproductive success by mating with as many different females as possible, there should be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
149
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(160 citation statements)
references
References 38 publications
9
149
1
1
Order By: Relevance
“…We found three independent components of variation in male behavior in the field: (1) courtship versus foraging, (2) dominance interactions, and (3) interference competition versus searching for mates (Table 1; also see Croft et al 2003). Each of these behavioral components varied among sites but only the third correlated with food availability in the field.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…We found three independent components of variation in male behavior in the field: (1) courtship versus foraging, (2) dominance interactions, and (3) interference competition versus searching for mates (Table 1; also see Croft et al 2003). Each of these behavioral components varied among sites but only the third correlated with food availability in the field.…”
Section: Discussionmentioning
confidence: 81%
“…We commonly observed aggression in the context of mating in the field at sites ranging from small, isolated pools with high guppy densities to larger streams with fastflowing currents and low guppy densities. Although males move among pools (Croft et al 2003), we sometimes resighted males on multiple visits. At the Marianne Tributary (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain why the UN guppies show the highest level of rheotaxis. Croft et al (2003) showed sex-biased dispersal in guppies, demonstrating a significant bias for upstream movement by males but not females. In addition, they found a positive correlation between body length and distance moved in females.…”
Section: Discussionmentioning
confidence: 95%
“…A total of 240 fish (120 large females (29.9G0.2 mm), 60 males (21.2G0.2 mm) and 60 small females (22.1G0.2 mm)) were individually marked with implant elastomer (see Croft et al 2003 for details) and tested in the enclosures in the mixed-or same-sex groups of 10 individuals across the study period. In the same-sex groups, small females were matched to the size of the males in the mixed-sex groups.…”
Section: K1mentioning
confidence: 99%